On another concept of literature - González Alcázar, Felipe (Razón y fe, 2020)
Over time, various concepts of literature have been sustained and continuously questioned. Besides the difficulty of a definition itself, the most important factor in this dissatisfaction has been to establish some limits between what is and is not Literature. The absence of the evaluative activity of criticism has helped to extend its nature to that of all other artistic communication, decreed by pragmatic studies. It aims to understand what is different based on a comparative concept of Literature without renouncing the evaluative work of criticism.
Keywords: literature; literary thought; critical appraisal; comparative studies